Pengaruh Media Big Book Terhadap Kemampuan Membaca Pemahaman Kelas IV di SD Negeri Gugus X Kota Bengkulu - Putri, Rahmadaniati; Susanti, Atika; Anggraini, Dwi (Universitas Bengkulu, 2026)
This study aims to determine the effect of Big Book media on the reading comprehension ability of fourth graders at the Tenth State Elementary School in Bengkulu City. This study is a type of quantitative research with a research method, namely the Quasi Experimental Design method with the Matching Only Pretest- Posttest Control Group Design research design. The population in this study were fourth grade students of the Tenth State Elementary School in Bengkulu City which were accredited B. The research sample was taken using the cluster random sampling technique, obtained fourth grade students of the 58th State Elementary School in Bengkulu City as the experimental group and fourth grade students of the 15th State Elementary School in Bengkulu City as the control group. The experimental group was given treatment using the Big Book media while the control group used conventional learning. The instrument used was a multiple-choice test sheet totaling 10 questions. The test was carried out twice, namely before and after learning took place in the experimental class and the control class. From the results of the t-test calculation of the students' post-test values, sig (2-tailed) 0.000 is smaller than 0.05. This shows that there is a difference in the post-test results between the experimental class and the control class which is caused by the different treatments of the two classes. So it can be concluded that there is an influence of Big Book media on the reading comprehension skills of fourth graders at the Tenth Cluster of State Elementary Schools in Bengkulu City.